Local Community, Volunteering and Tourism Development: The Case of The Blackwood River Valley, Western Australia - Alonso, Abel; Liu, Yi (Channel View Publications, 2013)
Rural communities, especially those that strive to become tourist destinations face many challenges, including limited human and financial resources in developing their own tourism sector. The importance of local visitor centres in promoting the region can be invaluable assets in addressing those limitations. However, to what extent can efforts among a community's residents also contribute towards the promotion of local tourism? The present study investigates this aspect of community involvement from the perspective of representatives (managers, staff) of an emerging rural tourism destination, the Blackwood River Valley in Western Australia. Semi-structured, face-to-face interviews were conducted in four visitor centres. Volunteerism among local residents in various ways of tourism promotion emerged as a key finding in this study, as well as volunteer work providing support beyond involvement at visitor centres. Indeed, this aspect of community involvement was further illustrated in other forms of community involvement (e.g. helping host and cater for events). The findings, therefore, reinforce the notion that through volunteerism, local residents make direct and indirect participatory contributions that help strengthen the social aspect, or social fabric, of the community, while contributing to tourism development.